POLITICAL ECONOMIC CORRELATION WITH POLITICS IN THE FIELD OF CRIMINAL LAW ENFORCEMENT - Rambey, Guntur (Proceeding International Seminar of Islamic Studies, 2023)
Activities in the economic sector require law as a basis and at the same time policy legitimacy to achieve national goals so that it is a necessity if the two disciplines of economics and law are seen as unable to ally in advancing the Indonesian people. Furthermore, according to Romli Atmasasmita, an economic analysis of law that uses the principle of maximization of balance (equilibrum) and efficiency (efficiency) with the "cose and benefit ratio" approach is expected to contribute to realizing legal ideals, certainty of justice and definite and measurable benefits. . The type of legal research that is carried out in a normative juridical manner is normative juridical where law is conceptualized as what is written in laws and regulations. The types of punishment applied to convicts tend to be conventional. Imprisonment sentences, fines, payment of compensation money, are some examples of the types of punishments imposed on convicts. However, no studies in Indonesia have been conducted to determine the extent to which these punishments are effective in reducing crime or deterring criminals.